The Role of Islamic Religious Counselors in Providing Religious Understanding of Ta'lim Councils in Minority Areas - Aliani, Syahrul Ode; Alam, Md. Shabbir; Rofiq, Ainur; Srinio, Fuad (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
Research Focus: (1) The role of PAI in providing religious understanding in Teluk Ambon District, Ambon City (2) PAI planning in providing religious understanding of the Taklim Assembly in Teluk Ambon District, Ambon City. This type of research uses Participatory Research with Qualitative Methods and a Case Study Approach. The results showed; (1) First, assisting and facilitating MT's operational letter. Second, provide solutions in dealing with religious problems in society. Third, provide information on the development of local potential with a lecture and recitation approach. Fourth, providing education based on religious materials needed in the community. (2) First, read and understand the material, and deliberate on determining expository and cooperative strategies. Second, it uses the interactive dialogue method and the lecture method. Third, evaluate strategies, methods, media, and materials. However, the evaluation of material achievements is only oral, and development in the form of Scientific Papers has never been carried out. (3) The existence of the Office of Religious Affairs as a forum for conducting deliberations in planning and evaluating the Islamic Extension Program. The inhibitors; are electronic media, distance, transportation, selection, and understanding of the material.